Experiences of Adults with Congenital Heart Disease: An Interpretative Phenomenological Analysis - Yaseen, Muhammad; Hasan, Gul; Bakhsh, Zuhra Lal (Pakistan Journal of Humanities and Social Sciences, 2023)
The study explored the understandings of young adults with congenital heart disease (CHD) having age range between 18-22 years and this study also investigated the coping behaviors. The Interpretative Phenomenological Analysis (IPA) was utilized in order to provide a detailed perception towards the experiences of the patients. Semi-structured interview was conducted with a voluntary sample of six participants who were diagnosed as CHD. The study highlighted Four main themes, such as loss of person identity and social distinctiveness, concerns about physical and future, negative emotions/thoughts, and adaptive and maladaptive coping behavior. Females experienced greater feeling of loss as compare to male, and were more concerned about the future occurrence of the disease, and they also stated severe adverse thoughts and emotions. Females sensed stress, and death anxiety; and the male was hopeful for the recovery. Adaptive coping style was applied by all the patients whether male or females. Afterward the recognition that preliminary managing styles were effective then they become optimistic and demanded for the family and peer support, they also applied social avoidance because they thought are incapable of social functioning. The research conducted in America or other western countries are found similar in result. Because they also applied care, support and treatment. Health care workers and therapists must realize the adverse psychosocial effects of young adults living with a heart disease and offer proper psychological and social support. Developments in care have upgraded the endurance and value of life for the young adults with CHD.